The influence of large classes in the English language teaching learning process in Ecuadorian high schools - Malo Toledo, Silvia Rosa Ana (2014)
Various researches have been done about the factors affecting the teaching of a language in a classroom. This thesis aims at finding out the influence of large classes in the English language teaching-learning process in Ecuadorian high schools, with the purpose of determining whether or not large classes affect the teaching-learning process. La Troncal, a small Town of the Province Cañar is the location where this important project has been carried out. The individuals that have taken part in this study were 210 students from different high schools around the City. Furthermore, quantitative and qualitative methods were used for the development of this research in order to interpret and discuss the academic, social and psychological data that has been gathered through the field research. In conclusion, having analyzed the results obtained in this research work, it can be stated that class size is not a barrier for a proper teaching and learning process even though certain aspects on academic, social and psychological issues might have an influence.